A Critique of the Decision in Conisbee that Vegetarianism Is Not 'A Belief'. (January 2020) - Cranmer, Frank; Sandberg, Russell
Abstract : Mr G Conisbee v Crossley Farms Ltd & Ors [2019] ET 3335357/2018 was a preliminary hearing to determine whether or not vegetarianism was 'capable of satisfying the requirement and definition of being a philosophical belief (protected characteristic) under the Equality Act 2010'. Employment Judge Postle held that vegetarianism did not amount to a philosophical belief, comparing it to veganism. The case is the latest in the confusing and contradictory case law on the meaning of the term 'religion or belief' under English law.